EXHUMATION OF HIGH-PRESSURE ROCKS UNDER CONTINUOUS COMPRESSION: A WORKING HYPOTHESIS FOR THE SOUTHERN HELLENIDES (CENTRAL CRETE, GREECE) - Chatzaras V.; Xypolias P.; Doutos T. (My University, 2006)
Combined kinematic, structural and palaeostress (calcite twinning, fault-slip data) analyses are used to study the exhumation mechanism of the high-pressure rocks exposed on the island of Crete (southern Aegean, Greece). Our study shows that the evolution of windows in central Crete was controlled by two main contractional phases of deformation. The first phase (D1) was related to the ductile-stage of exhumation. NNW-SSE compression during D1 caused layer- and transport-parallel shortening in the upper thrust sheets, resulting in nappe stacking via low-angle thrusting. Synchronously, intracontinental subduction led to high-pressure metamorphism which, however, did not affect the most external parts of the southern Hellenides. Subsequent upward ductile extrusion of high-pressure rocks was characterized by both down-section increase of strain and up-section increase of the pure shear component. The second phase (D2) was associated with the brittle-stage of exhumation. D2 was governed by NNE-SSW compression and involved conspicuous thrust-related folding, considerable tectonic imbrication and formation of a Middle Miocene basin. The major D2-related Psiloritis Thrust cross-cuts the entire nappe pile, and its trajectory partially follows and reworks the D1-related contact between upper and lower (high-pressure) tectonic units. Eduction and doming of the Talea Window was accompanied by gravity sliding of the upper thrust sheets and by out-of-the-syncline thrusting. Late-orogenic collapse also contributed to the exhumation process. Therefore, it seems that the high-pressure rocks of central Crete were exhumed under continuous compression and that the role of extension was previously overestimated. © 2006 Cambridge University Press.
Keywords: COMPRESSION TECTONICS; CRETE; EXHUMATION; HELLENIDES; HIGH-PRESSURE METAMORPHISM; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен